Analysis of the Potential of Regional Taxes on Regional Original Revenue (PAD) of East Lombok Regency for 2017-2021 - Hadi Mahmudi; Siti Fatimah (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to analyze the potential and contribution of local taxes to East Lombok Regency's Original Revenue (PAD) in 2017-2021. The method used in this study is a quantitative method with data sources originating from the Regional Breastfeeding Revenue Agency (BAPENDA) of East Lombok Regency. The data analysis technique used is the potential matrix (Overlay Analysis). The results of research on growth and contribution with potential matrix analysis (Overlay Analysis) in East Lombok Regency for 2017 – 2021 show that Restaurant Tax, Street Lighting Tax, Non-Metal and Rock Mineral Tax (MBLB), Rural and Urban Land and Building Tax (PBBP2) , and the Land and Building Rights Acquisition Fee Tax (BPHTB) is included in the prime category, this is due to the positive growth rate and high contribution. While the Rekalme Tax, Parking Tax, Underground Water Tax, and Swallow's Nest Tax are included in the developing category due to positive growth and low contribution. Taxes that fall into the underdeveloped category are hotel taxes and entertainment taxes, this is due to negative growth and low contributions.